Democratic Legal Principles in the Election of the Governor of NTB, Indonesia: Prinsip Hukum Demokratis dalam Pemilihan Penjabat Gubernur NTB, Indonesia - Azwar, Lalu Muhammad; Asmara, M. Galang; Purnomo, Chrisdianto Eko (Indonesian Journal of Law and Economics Review, 2024)
This study critically examines the mechanism of appointing the Acting Governor of Nusa Tenggara Barat (NTB), focusing on its alignment with the principles of a democratic legal state. Utilizing a normative legal research methodology, the study employs legislative and conceptual approaches, drawing from primary and secondary legal materials. The analysis incorporates descriptive analytical, prescriptive, and argumentative data analysis techniques. Findings reveal that the current mechanism, governed by the Ministry of Home Affairs Regulation No. 4 of 2023, mandates adherence to democratic legal state principles. However, it faces significant challenges in ensuring optimal public participation and safeguarding human rights (HAM). Although the process involves multiple stakeholders, including optional non-ministerial government agencies, the final decision remains centrally with the president. This centralistic tendency undermines direct public participation in political decision-making, a core tenet of democracy. Additionally, the mechanism lacks clear legal procedures for termination, posing a risk of violating HAM principles and affecting the legitimacy and continuity of the appointed official. The study recommends enhancing public and representative body involvement to better reflect democratic participation principles. It also suggests regulatory changes to mandate broader stakeholder involvement and establish clear termination mechanisms, thereby improving transparency, accountability, and legal certainty while upholding human rights protection. These improvements are crucial for bolstering the mechanism's democratic legitimacy and efficacy in NTB's governance.Highlights Centralized Authority: The president's ultimate decision-making power limits public involvement. Public Participation Gap: Insufficient societal engagement in the appointment process. Human Rights Risks: Unclear termination procedures pose legal and legitimacy concerns. Keywords: Democratic Legal Principles, Public Participation, Human Rights, NTB Governor Appointment, Legal Transparency